Hubungan Peran Perawat Sebagai Edukator Dengan Tingkat Kecemasan Pasien Pre Operatif Odontectomy - Vira Raisa Putri; Saiful Gunardi; Irma Herliana (Lembaga Pengembangan Kinerja Dosen, 2024)
Pre-operative odontectomy knowledge can reduce anxiety, prepare the patient physically and mentally, and facilitate pre-operative preparation. Anxiety can affect the surgical process. The role of nurses as educators is important to reduce anxiety by providing information about health, side effects of disease, and post-operative activities. The aim of the research was to determine the relationship between the role of nurses as educators and the anxiety level of pre-operative odontectomy patients at Hospital X, South Jakarta. The research method is observational analytic with a cross sectional design with a population of pre-operative odontectomy patients at Hospital X, South Jakarta and a sample size of 30 respondents. Data collection techniques use questionnaires and observational sheets. Data analysis used the Spearman Rank Correlation technique. The research results showed that the majority of nurses' roles were in the good category (63.3%) and the sufficient category (36.7%). Meanwhile, the majority of patients' anxiety levels were in the mild category (66.7%), moderate anxiety levels (20.0%) and severe anxiety levels (6.7%). The results of the Spearman-rank analysis test showed a p value <0.001, which means there is a significant relationship between the role of nurses as educators and the level of anxiety in pre-operative odontectomy patients at Hospital X, South Jakarta. The conclusion of the research is that there is a significant relationship between the role of nurses as educators and the level of anxiety in pre-operative odontectomy patients at Hospital X, South JakartaJakarta..